The role of exercise on long-term effects of alloxan administered in neonatal rats - de Oliveira, CAM; Luciano, E.; de Mello, MAR (Blackwell Publishing, 2005)
The present study was designed to analyse the effects of aerobic exercise on the metabolic effects of alloxan. Male Wistar newborn rats (2 days old) received alloxan (200 mg (kg body weight)(-1)) intraperitoneally (A rats). Vehicle-injected rats were used as controls (C rats). At 28 days old, some of the A rats were subjected to swimming for 1 h day(-1), 5 day week(-1) (AT rats). At 28, 60 and 90 days old the animals were subjected to glucose (GTTo) and insulin (ITTsc) tolerance tests. All the animals were then killed by decapitation for blood and tissue evaluations. on the 60th day, there was a reduction in blood glucose level during the GTTo (mmol l(-1) (90 min)(-1)) in the AT rats (7640.7+/-694.0) with respect to C (7057.5+/-776.9) and A (8555.6+/-1096.7) rats. However on the 90th day, AT rats showed higher glucose levels (8004.6+/-267.9) when compared to the other groups (C, 7305.5+/-871.2; A, 7088.8+/-536.9). The serum free fatty acid (FFA) concentration (muEq l(-1)) was higher in the alloxan-treated animals (A, 231.1+/-58.5; AT, 169.8+/-20.1) than in controls (C, 101.4+/-22.4). In conclusion, although the high blood glucose level is transitory in the A animals, some blood and tissue alterations remain and can be harmful to the maintenance of homeostasis. Physical exercise counteracted only partially these alterations. Furthermore, training worsened glucose tolerance at the 90th day, suggesting that exercise intensity should be adjusted to the diabetic condition.